Mulheres, autonomia e posse de bens: entre gênero e direito na Vila de Santa Cruz do Aracati (1778-1804) - Freitas, Joana Aymée Nogueira de (2025)
There is a difference involving the permissibility and prohibitions between men and women in the Portuguese laws that were applied in their colonies, characterizing clear legal asymmetries based on gender, especially regarding asset management. However, in the study of legal history, one cannot limit the sources to what is contained in written legislation. The objective of this research is to understand which legal institutes could influence the transmission of assets involving women in Portuguese America, more specifically in the Vila de Santa Cruz do Aracati. To meet this objective, it is analyzed mainly purchase and sale, donation and mortgage deeds, written between 1778 and 1804, found in the collection of the Aracati notary's office, alongside other sources such as requests to the Overseas Council and sesmarias dates. From the analysis of documentary sources, it can be seen that women in Portuguese America managed to assume an active and present role in colonial society, and it is not possible to summarize the law of this period to what was provided for in written regulations. Thus, it is not only possible to study these characters outside of the domestic and family contexts, but it can also be concluded that they could be responsible for relevant tasks, such as managing assets or executors of a deceased person's will.